2002
DOI: 10.1080/10446670290030981
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Macrophages in the Pathogenesis of Transmissible Spongiform Encephalopathies

Abstract: Although transmissible spongiform encephalopathies (TSE) or prion diseases are neurodegenerative disorders, the immune system is also involved, at least in the early stages of their pathogenesis. Extensive studies have focused on cells targeted by the TSE agent for its replication but few on the possible involvement of macrophages in its clearance, as in more conventional diseases. This review summarises some of the experiments aimed at demonstrating a role for macrophages in TSE and presents the application t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Two independent studies have shown that macrophages reduced prion infectivity during early infection (71,72), probably by degrading infectious prions. In a more recent study, it was found that mice deprived of TLR-4 developed accelerated scrapie, irrespective of which prion strain was injected and whether prions had been inoculated i.c.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies have shown that macrophages reduced prion infectivity during early infection (71,72), probably by degrading infectious prions. In a more recent study, it was found that mice deprived of TLR-4 developed accelerated scrapie, irrespective of which prion strain was injected and whether prions had been inoculated i.c.…”
Section: Discussionmentioning
confidence: 99%
“…1992; Jeffrey et al . 2000; Klein and Aguzzi 2000; Aucouturier and Carnaud 2002; Beringue et al . 2002; Perry et al .…”
Section: Signaling In the Immune Systemmentioning
confidence: 99%
“…Prion diseases or transmissible spongiform encephalopathies (TSEs) are neurodegenerative disorders that are characterized by loss of motor control, dementia, central nervous system (CNS) spongiosis, and microglial activation (1,2).…”
Section: Introductionmentioning
confidence: 99%